Neuromodulatory Inputs to Motoneurons Contribute to the Loss of Independent Joint Control in Chronic Moderate to Severe Hemiparetic Stroke - McPherson, Jacob G.; Ellis, Michael D.; Harden, R. Norman; Carmona, Carolina; Drogos, Justin M.; Heckman, Charles J.; Dewald, Julius P. A. (Frontiers in Neurology, 2018)
In chronic hemiparetic stroke, increased shoulder abductor activity causes involuntary increases in elbow, wrist and finger flexor activation, an abnormal muscle coactivation pattern known as the flexion synergy. Recent evidence suggests that flexion synergy expression may reflect recruitment of contralesional cortico-reticulospinal motor pathways following damage to the ipsilesional corticospinal tract. However, because reticulospinal motor pathways produce relatively weak post-synaptic potentials in motoneurons, it is unknown how preferential use of these pathways could lead to robust muscle activation. Here, we hypothesize that the descending neuromodulatory component of the ponto-medullary reticular formation, which uses the monoaminergic neurotransmitters norepinephrine and serotonin, serves as a gain control mechanism to facilitate motoneuron responses to reticulospinal motor commands. Thus, inhibition of the neuromodulatory component would reduce flexion synergy expression by disfacilitating spinal motoneurons. To test this hypothesis, we conducted a pre-clinical study utilizing two targeted neuropharmacological probes and inert placebo in a cohort of 16 individuals with chronic hemiparetic stroke. Test compounds included Tizanidine, a noradrenergic α2 agonist and imidazoline ligand selected for its ability to reduce descending noradrenergic drive, and Isradipine, a dihyropyridine calcium-channel antagonist selected for its ability to post-synaptically mitigate a portion of the excitatory effects of monoamines on motoneurons. We used a previously validated robotic measure to quantify flexion synergy expression. We found that Tizanidine significantly reduced expression of the flexion synergy. A predominantly spinal action for this effect is unlikely because Tizanidine is an agonist acting on a baseline of spinal noradrenergic drive that is likely to be pathologically enhanced post-stroke due to increased reliance on cortico-reticulospinal motor pathways. Although spinal actions of TIZ cannot be excluded, particularly from Group II pathways, our finding is consistent with a supraspinal action of Tizanidine to reduce descending noradrenergic drive and disfacilitate motoneurons. The effects of Isradipine were not different from placebo, likely related to poor central bioavailability. These results support the hypothesis that the descending monoaminergic component of the ponto-medullary reticular formation plays a key role in flexion synergy expression in chronic hemiparetic stroke. These results may provide the basis for new therapeutic strategies to complement physical rehabilitation.